Anion exchange membrane with strong acid and alkali resistance and weak alkali type as well as preparation method and application of anion exchange membrane
By introducing porphyrin branched structure into the weak alkaline anion exchange membrane, the problems of insufficient acid resistance and high resistance of the membrane under alkaline conditions are solved, and the effects of high acid and alkali resistance and low resistance are achieved, which are suitable for electrodialysis desalination process.
Patent Information
- Application Number
- CN202510040255.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-10
- Publication Date
- 2025-04-15
AI Technical Summary
The existing weakly alkaline anion exchange membranes have insufficient acid resistance and high resistance under alkaline conditions, making them difficult to be used in the electrodialysis desalination process.
By introducing porphyrin branched structure into the membrane material, the hydrophilicity of the weakly alkaline backbone is improved, and the pH response characteristics of the porphyrin structure are utilized to reduce the resistance of the membrane and improve acid and alkali resistance.
It realizes the high acid-base resistance, low resistance and good desalting properties of weak alkali anion exchange membrane, and can maintain stable performance during long-term strong acid-base soaking.
Smart Images

Figure BDA0005236720670000031
Abstract
Description
Technical Field
[0001] The invention relates to a strong acid and alkali resistant weak base type anion exchange membrane and a preparation method and application thereof, belonging to the technical field of electrodialysis. Background Art
[0002] Traditional anion exchange membranes usually use quaternary ammonium salts as ionic groups, which are prone to Hofmann degradation under alkaline conditions, resulting in material inactivation. This problem needs to be solved urgently.
[0003] Although the use of weakly alkaline tertiary amine groups as ion exchange groups does improve the membrane's alkali resistance, at the same time, the membrane's conductivity will drop significantly. After the commercial ACM membrane (tertiary amine type) is activated in an acidic environment, although the resistance during the electrodialysis desalination process is reduced, it is still high, and the ACM membrane itself is designed for an acidic environment. Therefore, there are two key issues that need to be addressed: first, how can the weakly alkaline anion exchange membrane achieve sufficient alkali resistance; second, how to reduce the resistance of the weakly alkaline anion exchange membrane. In-depth research on these two issues is expected to develop acid- and alkali-resistant anion exchange membranes with superior performance.
[0004] Polyaryl piperidine exhibits strong alkali resistance due to its ether-free main chain. The researchers prepared a series of alkali-resistant anion exchange membranes by modifying it, but most of them are still strong alkaline anion exchange membranes. When the polyaryl piperidine membrane is not quaternized, although the material has good alkali resistance, it is difficult to use in the desalination process due to its high resistance. After being treated in an acidic environment, the water absorption of the membrane is significantly enhanced, and it shows strong stability during the electrodialysis process, so that it can be used for electrodialysis desalination on a par with the AMX membrane. However, the resistance problem remains prominent, and the solution to this key problem is still not perfect. Summary of the invention
[0005] The purpose of the present invention is to overcome the shortcomings of the prior art and provide a method for preparing a strong acid-base resistant weak base anion exchange membrane. The strong acid-base resistant weak base anion exchange membrane of the present invention has acid-base resistance, low resistance, visualized pH response and good desalination performance.
[0006] In order to achieve the above-mentioned invention object, the present invention adopts the following technical scheme:
[0007] In a first aspect, an embodiment of the present invention provides a method for preparing a strong acid-base-resistant weak-base anion exchange membrane, comprising the following steps:
[0008] (1) Dissolve 3-5 g of biphenyl, 4-5 mL of N-methyl-4-piperidone and 0.01-0.2 g of tetraphenylporphyrin in 5-20 mL of dichloromethane;
[0009] (2) under ice bath conditions, 1-3 mL of trifluoroacetic acid is added dropwise to the mixed solution obtained in step (1) at a constant rate, and 10-33 mL of trifluoromethanesulfonic acid is added, and the reaction is continued for 3-5 hours;
[0010] (3) pouring the green viscous mixture obtained in step (2) into deionized water for elution to obtain a solid;
[0011] (4) dissolving 0.5-1 g of the solid obtained in step (3) in 10-15 mL of a casting solvent to obtain a green transparent solution;
[0012] (5) Pour the green transparent solution in step (4) onto a glass plate, place it in a vacuum drying oven, and dry it at 60-80° C. for 10-24 h to obtain a weakly alkaline anion exchange membrane.
[0013] Furthermore, in step (4), the film casting solvent is one or more of dimethyl sulfoxide, N,N-dimethylacetamide and N,N-dimethylformamide.
[0014] Furthermore, in step (5), the thickness of the weakly alkaline anion exchange membrane is controlled to be 80-110 μm.
[0015] Furthermore, in step (3), when eluting with deionized water, elution is performed 3-5 times to ensure that the residual solvent is completely eluted.
[0016] Furthermore, the strong acid-base resistant weak base anion exchange membrane is soaked in an acidic aqueous solution before use, for example, in a 0.1 mol / L dilute hydrochloric acid solution for 3-6 hours.
[0017] In a second aspect, an embodiment of the present invention provides a weak base anion exchange membrane with strong acid and alkali resistance, which is prepared by the preparation method described in the first aspect.
[0018] In a third aspect, an embodiment of the present invention provides the use of the strong acid and alkali resistant weak base anion exchange membrane described in the second aspect as a membrane material for electrodialysis desalination.
[0019] The technical solution provided by the embodiment of the present invention has the following beneficial effects:
[0020] 1) The strong acid and alkali resistant weak base anion exchange membrane prepared by the preparation method of the present invention has excellent desalination performance, which is comparable to that of the strong base anion exchange membrane.
[0021] 2) The strong acid and alkali resistant weak base anion exchange membrane prepared by the present invention has good acid and alkali resistance. After long-term immersion in strong acid and alkali, the performance of the membrane remains basically unchanged.
[0022] 3) The strong acid- and alkali-resistant weak-base anion exchange membrane prepared by the preparation method of the present invention has good pH response visualization and can quickly reflect the state of the solution during the electrodialysis process.
[0023] 4) The weakly alkaline anion exchange membrane prepared by the present invention has a simple preparation process, does not require quaternization, has simple synthesis steps, and is easy to industrialize. DETAILED DESCRIPTION
[0024] In order to make the purpose, technical solution and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.
[0025] Example 1
[0026] A method for preparing a strong acid and alkali resistant weak base anion exchange membrane comprises the following steps:
[0027] (1) Dissolve 4.2 g of biphenyl, 4.1 mL of N-methyl-4-piperidone and 0.02 g of tetraphenylporphyrin in 10 mL of dichloromethane;
[0028] (2) under ice bath conditions, 2 mL of trifluoroacetic acid was added dropwise to the mixed solution obtained in step (1) at a constant rate, and then 25 mL of trifluoromethanesulfonic acid was added, and the reaction was continued for 4 hours;
[0029] (3) pouring the green viscous mixture obtained in step (2) into deionized water for elution to obtain a colored solid (the green color will become darker as the amount of tetraphenylporphyrin increases);
[0030] (4) 0.75 g of the solid polymer obtained in step (3) was dissolved in 15 mL of dimethyl sulfoxide to obtain a green transparent solution;
[0031] (5) The green transparent solution was poured onto a glass plate, placed in a vacuum drying oven, and dried at 80° C. for 24 h to obtain a weakly alkaline anion exchange membrane AEM-1.
[0032] Example 2
[0033] A method for preparing a strong acid and alkali resistant weak base anion exchange membrane comprises the following steps:
[0034] (1) Dissolve 4.2 g of biphenyl, 4.1 mL of N-methyl-4-piperidone and 0.04 g of tetraphenylporphyrin in 10 mL of dichloromethane;
[0035] (2) under ice bath conditions, 2 mL of trifluoroacetic acid was added dropwise to the mixed solution obtained in step (1) at a constant rate, and then 25 mL of trifluoromethanesulfonic acid was added, and the reaction was continued for 4 hours;
[0036] (3) pouring the green viscous mixture obtained in step (2) into deionized water for elution to obtain a colored solid (the green color will become darker as the amount of tetraphenylporphyrin increases);
[0037] (4) 0.75 g of the solid polymer obtained in step (3) was dissolved in 15 mL of dimethyl sulfoxide (DMSO) to obtain a green transparent solution;
[0038] (5) The green transparent solution was poured onto a glass plate, placed in a vacuum drying oven, and dried at 80° C. for 24 h to obtain a weakly alkaline anion exchange membrane AEM-2.
[0039] Example 3
[0040] A method for preparing a strong acid and alkali resistant weak base anion exchange membrane comprises the following steps:
[0041] (1) Dissolve 4.2 g of biphenyl, 4.1 mL of N-methyl-4-piperidone and 0.1 g of tetraphenylporphyrin in 10 mL of dichloromethane;
[0042] (2) under ice bath conditions, 2 mL of trifluoroacetic acid was added dropwise to the mixed solution obtained in step (1) at a constant rate, and then 25 mL of trifluoromethanesulfonic acid was added, and the reaction was continued for 4 hours;
[0043] (3) pouring the green viscous mixture obtained in step (2) into deionized water for elution to obtain a colored solid (the green color will become darker as the amount of tetraphenylporphyrin increases);
[0044] (4) 0.75 g of the solid polymer obtained in step (3) was dissolved in 15 mL of dimethyl sulfoxide (DMSO) to obtain a green transparent solution;
[0045] (5) The green transparent solution was poured onto a glass plate, placed in a vacuum drying oven, and dried at 80° C. for 24 h to obtain a weakly alkaline anion exchange membrane AEM-3.
[0046] The performance of the anion exchange membranes prepared in Examples 1-3 was tested below:
[0047] Test 1: The weakly alkaline anion exchange membranes prepared in Examples 1-3 were subjected to resistance tests and compared with commercial quaternary ammonium type AMX and tertiary amine type ACM anion exchange membranes.
[0048] Table 1 Comparison of membrane surface resistance between the weakly alkaline anion exchange membrane prepared in Examples 1-3 and the commercial membrane
[0049]
[0050] As can be seen from Table 1, the tertiary amine anion exchange membrane prepared in Examples 1-3 forms a hydrophilic channel while the high molecular polymer forms a branched structure due to the presence of the porphyrin supramolecular structure. Under direct test conditions, it shows significantly lower resistance, which is particularly prominent compared to the traditional tertiary amine ACM anion exchange membrane. After activation by an acidic solution, its performance is even comparable to that of the quaternary ammonium anion exchange membrane AMX. This shows that the tertiary amine anion exchange membrane can efficiently respond to pH changes and significantly reduce energy consumption.
[0051] Test 2: The chemical stability of the prepared anion exchange membrane in sodium hydroxide solution was tested to investigate the chemical stability of the anion exchange membrane. The weight loss rate was used as an indicator and the weight difference was used as an indicator to evaluate its chemical stability. After being completely dried in a vacuum oven at 80°C for 24 hours, the weight of the sample was recorded. Then, the dried ion exchange membrane sample was soaked in a 2.0M sodium hydroxide solution at 80°C for 24 hours, 48 hours, and 96 hours, and then the retained solution on the surface of the sample was carefully wiped, and the soaked membrane was washed with water until the water became neutral. Then, the ion exchange membrane sample was dried at 80°C under vacuum conditions for 24 hours, and then the membrane mass was re-weighed. The mass loss was used to characterize the alkali resistance stability. The test method in 2M sulfuric acid is the same as above.
[0052] Table 2 Weight loss rate of membranes immersed in 2.0 mol / L sodium hydroxide solution at different time periods
[0053] Time (h) 24 48 96 AMX weight loss rate (%) 10.2 15.2 19.3 AEM-1 weight loss rate (%) 1.1 1.2 1.4 AEM-2 weight loss rate (%) 1.2 1.3 1.4 AEM-3 weight loss rate (%) 1.1 1.2 1.3
[0054] As can be seen from Table 2, the conventional quaternary ammonium anion exchange membrane AMX often loses weight to a certain extent due to Hofmann degradation. However, the tertiary amine anion exchange membrane prepared in Examples 1-3 exhibits a lower weight loss rate due to its unique stability structure and the characteristics of the tertiary amine functional group, further highlighting its superior chemical stability.
[0055] Table 3 Weight loss rate of membranes immersed in 2.0 mol / L sulfuric acid solution at different time periods
[0056] Time (h) 24 48 96 AMX weight loss rate (%) 3.23 4.21 6.33 AEM-1 weight loss rate (%) 1.31 1.43 1.67 AEM-2 weight loss rate (%) 1.22 1.36 1.43 AEM-3 weight loss rate (%) 1.34 1.52 1.58
[0057] As can be seen from Table 3, the conventional quaternary ammonium anion exchange membrane AMX is formed by double bond copolymerization and other methods, so its oxidation resistance is relatively weak, so that the membrane has a certain weight loss in a strong acid solution. The tertiary amine anion exchange membrane prepared in Examples 1-3 exhibits a lower weight loss rate due to its unique stability structure and the characteristics of the tertiary amine functional group, further highlighting its superior chemical stability.
[0058] Test 3: Compare the water absorption of the prepared anion exchange membrane with that of AMX at different temperatures. After the tested membrane sample is completely dried in a vacuum drying oven at 80°C for 24 hours, the length of the membrane sample is recorded. Then, the dried ion exchange membrane sample is soaked at 20°C, 30°C, and 40°C for 48 hours. Then, the retained solution on the surface of the sample is carefully wiped off, and the weight of the membrane sample is recorded. Calculate the weight change of the sample compared to the dry state.
[0059] Table 4 Water absorption of anion exchange membrane and AMX membrane prepared in Examples 1-3 at different temperatures
[0060] Sample No. 20℃(%) 30℃(%) 40℃(%) AMX 21.13 26.62 32.82 AEM-1 5.05 7.58 8.38 AEM-2 7.12 9.18 10.23 AEM-3 8.77 10.21 11.23
[0061] As can be seen from Table 4, the anion exchange membranes prepared in Examples 1-3 have a rigid polymer skeleton, and their water absorption rate changes when the temperature rises are far less significant than that of the AMX membrane with a flexible polymer chain structure. This shows that the anion exchange membranes prepared in Examples 1-3 have good thermal stability and are not easily deformed by heat, thus showing excellent structural stability in a high temperature environment.
[0062] From the desalination process of electrodialysis, due to the low water absorption of tertiary amine type membrane groups, there are fewer hydrophilic channels in the membrane, which leads to the problem of excessive resistance. Therefore, in order to improve the alkali resistance of the membrane and reduce the resistance of the membrane, the present invention starts with the structural design of the membrane, and modifies the membrane material by adding branched structures such as porphyrin. Unlike traditional cross-linking agents, the branched structure of the main chain makes the winding of the molecular chain no longer tight, which can improve the hydrophilicity of the weakly alkaline main chain. More importantly, the porphyrin structure can respond to pH changes. The membrane is green under acidic conditions and red under alkaline conditions. This characteristic gives the prepared membrane a visualization effect, which helps to observe the changes in the hydrophilic and hydrophobic states of the membrane, making it more adaptable to different environmental conditions.
[0063] The hydrophilicity of the weakly alkaline anion exchange membrane is improved by adding porphyrin branching structures, thereby effectively reducing its resistance. This modification method requires a small amount of porphyrin to be added, has good prospects for large-scale production, and opens a new chapter in the application of weakly alkaline anion exchange membranes in desalination.
[0064] Finally, it should be noted that the above specific implementation methods are only used to illustrate the technical solution of the present invention rather than to limit it. Although the present invention has been described in detail with reference to examples, those skilled in the art should understand that the technical solution of the present invention can be modified or replaced by equivalents without departing from the spirit and scope of the technical solution of the present invention, which should be included in the scope of the claims of the present invention.
Claims
1. A method for preparing a strong acid- and alkali-resistant weak-base anion exchange membrane, characterized in that: The steps include: (1) Dissolve 3-5 g of biphenyl, 4-5 mL of N-methyl-4-piperidone and 0.01-0.2 g of tetraphenylporphyrin in 5-20 mL of dichloromethane; (2) under ice bath conditions, add 1-3 mL of trifluoroacetic acid and 10-33 mL of trifluoromethanesulfonic acid to the mixture obtained in step (1) at a constant rate, and continue the reaction for 3-5 hours; (3) pouring the green viscous mixture obtained in step (2) into deionized water for elution to obtain a solid; (4) Dissolve 0.5-1 g of the solid obtained in step (3) in 10-15 mL of a casting solvent to obtain a green transparent solution; (5) Pour the green transparent solution in step (4) onto a glass plate, place it in a vacuum drying oven, and dry it at 60-80° C. for 10-24 h to obtain a weakly alkaline anion exchange membrane.
2. The method for preparing the strong acid and alkali resistant weak base anion exchange membrane according to claim 1, characterized in that: In step (4), the film casting solvent is one or more of dimethyl sulfoxide, N,N-dimethylacetamide and N,N-dimethylformamide.
3. The method for preparing the strong acid and alkali resistant weak base anion exchange membrane according to claim 1, characterized in that: In step (5), the thickness of the weakly alkaline anion exchange membrane is controlled to be 80-110 μm.
4. The method for preparing the strong acid and alkali resistant weak base anion exchange membrane according to claim 1, characterized in that: In step (3), when eluting with deionized water, elute 3-5 times to ensure that the residual solvent is completely washed away.
5. The method for preparing the strong acid and alkali resistant weak base anion exchange membrane according to claim 1, characterized in that: The strong acid and alkali resistant weak base type anion exchange membrane is soaked in an acidic aqueous solution before use.
6. A strong acid and alkali resistant weak base anion exchange membrane, characterized in that: The method is prepared by the preparation method according to any one of claims 1 to 5.
7. The use of the strong acid and alkali resistant weak base anion exchange membrane according to claim 6, characterized in that: As membrane material for electrodialysis desalination.
Citation Information
Patent Citations
Preparation method of porphyrin / nano porous fiber membrane hydrogen chloride gas sensor
CN106442497A
Branched poly (aryl piperidinium) anion exchange membrane as well as preparation method and application thereof
CN115678073A
Hyperbranched anion exchange membrane as well as preparation method and application thereof
CN116731366A
Anion exchange membrane and method for producing same
CN116801967A